Enhanced Expression of Cell-Specific Surface Antigens on Endothelial Microparticles in Sepsis-Induced Disseminated Intravascular Coagulation. Issue 5 (May 2015) - Matsumoto, Hisatake; Yamakawa, Kazuma; Ogura, Hiroshi; Koh, Taichin; Matsumoto, Naoya; Shimazu, Takeshi
Abstract : ABSTRACT: Sepsis-induced disseminated intravascular coagulation (DIC) is a major cause of death in patients admitted to intensive care units. Endothelial injury with microparticle production is reported in the pathogenesis of sepsis. Endothelial microparticles (EMPs) present several cell-specific surface antigens with different bioactivities, for example, tissue factor (TF), thrombomodulin (TM), and endothelial protein C receptor (EPCR). We investigated associations between these three different surface antigen–positive EMPs and sepsis-induced DIC. This cross-sectional study composed of 24 patients with sepsis and 23 healthy controls was conducted from November 2012 to September 2013. Blood samples were collected from patients within 24 h of diagnosis of severe sepsis and from healthy controls. Numbers of TF-positive EMPs (TF + EMPs), TM-positive EMPs (TM + EMPs), and EPCR-positive EMPs (EPCR + EMPs) were measured by flow cytometry immediately thereafter. Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment scores were assessed in the severe sepsis patients at enrollment. We assessed DIC with the International Society of Thrombosis and Haemostasis (ISTH) overt DIC diagnostic criteria algorithm. Numbers of antigen-positive EMPs were increased significantly in both severe sepsis patients and controls and with the increase in ISTH DIC score. Numbers of TF + EMPs and EPCR + EMPs correlated significantly with Sequential Organ Failure Assessment score, and numbers of EPCR + EMPs correlated significantly with Acute Physiology and Chronic Health Evaluation II score. Numbers of the three antigen-positive EMPs were increased significantly in severe sepsis patients versus those in healthy controls and with the increase of ISTH DIC score, suggesting that the specific bioactivity of each antigen-positive EMP may play a role in the progression of sepsis-induced DIC.